THE INFLUENCE OF CULTURALLY RESPONSIVE TEACHING THROUGH VALUES, CULTURE AND CHARACTER EDUCATION ON STUDENTS' MATHEMATICS LEARNING OUTCOMES - Kurniawan, Dian; Madawistam, Sri Tirto; Heryani, Yeni (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Culturally responsive teaching (CRT) is a pedagogical approach that uses the cultural characteristics, experiences and perspectives of ethnically diverse children as a way to achieve these goals in order to teach more effectively. Meaningful learning is expected to grow through values, culture and character education. This research aims to determine the influence of Culturally Responsive Teaching through values, culture and character education on the Mathematics Learning Outcomes of students in class 7 of SMPN 8 Banjar for the 2023/2024 academic year. This research uses Pre-Experimental Design with a One Group Pretest-Posttest Design research design. The sample in this study was 34 grade 7 students consisting of 14 female students and 20 male students. The data collection technique used in this research is observation. Test data about questions using culturally responsive teaching shows an average pre-test score of 35.44, while the average post-test score is 81.62. Both variances are normally distributed using Kolmogorov-Smirnov with a significance value (sig.) pretest-posttest value 70 is 0.069, value 75 is 0.200, value 80 is 0.200, value 85 is 0.200, and value 90 is 0.084, while using Shapiro-Wilk values The pretest-posttest significance (Sig.) with a score of 70 is 0.228, a score of 75 is 0.782, a score of 80 is 0.314, a score of 85 is 0.314, and a score of 90 is 0.347. Both have the same variance (homogeneous) using Levene's test with an average significance value (sig.) above 0.900, thus the significance value for the normality test and homogeneity test is > 0.05. Culturally Responsive Teaching can improve mathematics learning outcomes based on the results of the Paires Sample T-Test calculation with a significance value of 0.00 < 0.05 so it can be said that there has been an improvement.